Ketogenic diet with aerobic exercise can induce fat browning: potential roles of β-hydroxybutyrate - Kim, Sujin; Park, Dong-Ho; Moon, Sohee; Gu, Bonsang; Mantik, Keren Esther Kristina; Kwak, Hyo-Bum; Ryu, Ji-Kan; Kang, Ju-Hee (Frontiers in Nutrition, 2024)
Introduction: Despite evidence suggesting that metabolic intermediates like β-HB influence white adipose tissue (WAT) metabolism, the precise molecular mechanisms remain unclear. The aim of this study was to investigate the impact of beta-hydroxybutyrate (β-HB) on the fat browning program and to explore the underlying molecular mechanisms using both in vitro and in vivo models. We assessed the effects of β-HB on fat browning in adipocytes using 3T3-L1 cells and rat models. Methods: We evaluated the effects of β-HB on fat browning, thermogenesis, lipid accumulation, adipokine expression, and mitochondrial biogenesis by treating mature 3T3-L1 adipocytes with sodium β-HB for 24 hours or by continuously exposing preadipocytes to β-HB during the 8-day differentiation process. We evaluated the effects of β-HB on fat browning and thermogenesis, lipid accumulation, adipokine expression, and mitochondrial biogenesis in 3T3-L1 cells. Male Sprague Dawley rats were divided into control, exercise only (EX), ketogenic diet only (KD), and combined exercise and ketogenic diet (KE) groups for an 8-week intervention involving diet and/or exercise. After intervention, we evaluated WAT histology, plasma lipids and adipokines, and the expression of markers related to fat browning, thermogenesis and mitochondrial biogenesis in WAT of rats. Results: In our adipocyte culture experiments, β-HB reduced intracellular lipid accumulation by enhancing lipolysis and stimulated the expression of thermogenic and fat browning genes like uncoupling protein 1 (UCP1), PR domain containing 16 (PRDM16), and adipokines such as fibroblast growth factor 21 (FGF21) and Fibronectin type III domain-containing protein 5 (FDNC5). Additionally, β-HB activated the AMPK-SIRT1-PGC-1α pathway, with UCP1 and PRDM16 upregulation mediated by β-HB intracellular action and SIRT1 activity. In animal experiments, KE group raised β-HB levels, decreasing body weight and blood lipids. KD with EX promoted WAT browning possibly via AMPK-SIRT1-PGC-1α, augmenting PRDM16, UCP1, FGF21, and FNDC5 expression. Conclusion: β-HB induction via KD and/or EX shows potential in promoting WAT browning by activating mitochondrial biogenesis, lipolysis, and thermogenesis, suggesting that dietary and physical intervention inducing β-HB may benefit metabolic health.